2006
DOI: 10.1002/jlcr.1052
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis of [11C]ureas via triphenylphosphinimines

Abstract: SummaryA series of 11 C-labeled ureas was prepared using a rapid and efficient one-pot procedure. First, the intermediate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
(46 reference statements)
2
37
0
1
Order By: Relevance
“…44 Phenyltriphenylphosphinimine could be used to prepare [ 11 C- carbonyl ]phenylisocyanate, and a variety of unsymmetrical 11 C-ureas from aliphatic and aromatic amines (Scheme 2B). 45 In this case, [ 11 C]CO 2 was trapped in a THF solution cooled to −60 °C during gas delivery, followed by heating to 60 °C to complete the reaction. Given the high trapping efficiency in the absence of base, it is likely that [ 11 C]CO 2 forms a complex with either the phosphinimine or amine precursor.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…44 Phenyltriphenylphosphinimine could be used to prepare [ 11 C- carbonyl ]phenylisocyanate, and a variety of unsymmetrical 11 C-ureas from aliphatic and aromatic amines (Scheme 2B). 45 In this case, [ 11 C]CO 2 was trapped in a THF solution cooled to −60 °C during gas delivery, followed by heating to 60 °C to complete the reaction. Given the high trapping efficiency in the absence of base, it is likely that [ 11 C]CO 2 forms a complex with either the phosphinimine or amine precursor.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…While reactive enough to add to phosgene, N-sulfinylamines are poor nucleophiles, thus suppressing further addition of amine to the generated [ [14] . [17] No additional examples were given and the method may be limited to aromatic amines and constrained by the lack of structurally diverse triphenylphosphinimines. Recently Hooker et al and our group reported that [ 11 C]CO 2 can be efficiently trapped at ambient temperature and pressure in small volumes of solvent using 1,…”
Section: Introductionmentioning
confidence: 99%
“…Symmetric ureas have been prepared directly from [ 11 C]carbon dioxide and the corresponding amine 11. Reactive triphenylphosphine imines and [ 11 C]carbon dioxide gave moderate yields of [ 11 C]ureas when strong nucleophiles were used, and lower yields when the weak nucleophile aniline (110 mM) was used 12…”
Section: Introductionmentioning
confidence: 99%